The Adomian Decomposition Method with Discretization for Second Order Initial Value Problems - Dagnachew Mengstie Tefera; Awoke Andargie ((IJCSAM) International Journal of Computing Science and Applied Mathematics, 2019)
In this paper, Adomian Decomposition Method with Discretization (ADMD) is applied to solve both linear and nonlinear initial value problems (IVP). Comparison with Adomian Decomposition Method (ADM) is presented. To illustrate the efficiency and accuracy of the method, five examples are considered. The result shows that ADMD is more efficient and accurate than ADM.